Analisis Pengendalian Kualitas Produk Tas Spunbond Menggunkan Metode Seven Tools dan Kaizen - Triamanda, Dika Yunita; Sumiati, Sumiati (Universitas Nahdlatul Ulama Blitar, 2025)
CV. XYZ is a company that produces various types of spunbond bags. In the production process, the company still experiences problems related to the number of defective products, namely 5%. This research aims to determine the level of defects and factors causing defects using the Seven Tools method, as well as providing suggestions for improvements to reduce the level of defects using the Kaizen 5M Checklist and Kaizen 5S methods. The most common levels of spunbond bag product defects were 8762 pcs of bad screen printing defects, 5059 pcs of sloppy stitching defects, 3715 pcs of dirty defects and 3548 wrong cutting defects. Factors that cause product defects are lack of accuracy and skill of workers, lack of compliance with production methods or standard operating procedures (SOP), equipment and lighting conditions that are not optimal, and work environments that are less than clean. In this way, several recommendations for improvements in human factors, machines, raw materials, methods and work environment are proposed, as well as the implementation of 5S (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke).